Jakościowe czynniki efektywności procesu świadczenia usług szpitalnych: Qualitative factors of the efficiency of hospital services - Bober, Benedykt; Olkiewicz, Marcin (Management and Administration Journal, 2021)
This paper presents possible implications of the qualitative assessment of the process of effectiveness in the area of hospital services provision. Infrastructure and diagnostic equipment in analyzed units are an important factor of qualitative evaluation of the effectiveness of public hospitals, and the use of the technology by highly qualified staff (interdisciplinary teams) is more vital than the mere availability of that technology.